Financial fraud contagion through board interlocks: the contingency of status. Issue 2 (9th December 2019) - Jiang, Yusi; Zhao, Yapu
Abstract : Purpose: The purpose of this paper is to explore the implications of the relative status between two interlocking firms for financial fraud or non-fraud contagion through interlock ties. Design/methodology/approach: This study uses a sample of publicly listed firms in China over a ten-year period from 2005 to 2014. Data are collected from the China Stock Market and Accounting Research Database. Findings: This study finds that non-fraud behaviors of lower-status partners inhibit fraud behaviors of the focal firm, whereas their fraud behaviors have no effect on the focal firm. In contrast, fraud behaviors of higher-status partners facilitate fraud behaviors of the focal firm, whereas their non-fraud behaviors have no effect on the focal firm. Originality/value: This study provides new insights to the misconduct contagion literature by considering firms' status differential as an important factor that governs the contagion process of fraud or non-fraud behaviors in board interlocks. It combines role theory and the contagion literature by studying the influence of the match between the status-based role expectations and practices of interlocking firm on the focal firm's decision to engage in the same type of practice.